Pengaruh Discount, Store Layout, dan Display Product terhadap Impulsive Buying pada Konsumen Pakaian Brand ADA di Kediri - Melynda, Fitria (Jurnal Cendekia Manajemen (JCM); Vol 1 No 2 (2023): JulyDO - 10.32503/jcm.v1i2.4376, 2023)
This research aims to determine and explain the influence of discounts, store layout and product displays on impulsive buying among consumers of "ADA" brand clothing in Kediri. This type of research is quantitative research. This research was conducted by distributing questionnaires to 153 respondents. The sampling technique used is simple random sampling. This research uses the SPSS 25 program in the data analysis process. The analysis techniques used are multiple linear regression analysis, t test, F test and classical assumption test. Based on the results of the t test, discounts, store layout and product display partially have a significant effect on impulsive buying among consumers of "ADA" brand clothing in Kediri. Based on the results of the F test, it shows that the calculated F value is 101.276 > F table is 2.67 with a significance of 0.000 â‰¤ 0.05. So it can be said that the discount, store layout and product display variables have a significant effect on impulsive buying among consumers of "ADA" brand clothing in Kediri. Meanwhile, the contribution given by the discount, store layout and product display variables to impulsive buying among consumers of "ADA" brand clothing in Kediri is 67.1%, which is known from the results of the coefficient of determination test. Keywords : Discount, Store Layout, Product Display and Impulsive Buying.